Adsorption technology and design - Thomas, W. J.
Adsorption is of considerable industrial importance and is a major part of many different processes throughout the chemical and process industries, including many reactions - chemical and bio-chemical, purification and filtration, gas and liquid processing and catalysis. Adsorption is a complex process and this makes the correct design and implementation of its operation all the more critical. The aim of this book is to provide all those involved in designing and running adsorption processes with a straightforward guide to the essentials of adsorption technology and design.